Herb mocktail product innovation to improve the creative economy in Wilayut Village - Ramon Ananda Paryontri; Lely Ika Mariyati; Safia Meilia Sari; Nur Azmi Widyastuti (Community Empowerment, 2022)
Herb products have become people's daily consumption. However, herb products are often considered old-fashioned and conventional accompanied by poor packaging. This happens because of the lack of knowledge and skills of herb medicine business players in developing processed products, packaging, and marketing. The purpose of this activity is to increase the knowledge and skills of the PKK group in making the innovative "JAJEKUA" herb mocktail product and has good packaging. Meanwhile, branding socialization aims to make the target community have skills in product marketing to achieve stable sales in the long term. The method used is training with discussions, presentations, house-to-house assistance, and making videos of the herb medicine-making process. This activity provides great benefits as indicated by an increase in knowledge and skills in making mocktail "JAJEKUA" herb medicine products and the ability to package good products.